Prevalence of Trypanosoma cruzi infection in dogs in the United States: a systematic review and meta-analysis of observational studies (2000–2024) - Agbajelola, Victor; Roachell, Walter; Bast, Joshua; Lenhart, Paul; Solis, Mauricio; Raghavan, Ram K. (Frontiers in Veterinary Science, 2025)
BackgroundCanine infection with Trypanosoma cruzi, the causative agent of Chagas disease, is a public health concern in the United States (U.S.), particularly in southern states where triatomine vectors are established. Dogs are considered important in the transmission cycle as potential reservoir hosts, with implications for both animal and human health. This study systematically reviewed observational studies to assess the prevalence, geographic distribution, and associated risk factors of canine T. cruzi infection in the U.S., and generated pooled prevalence estimates through meta-analysis.MethodsA systematic review and meta-analysis were conducted in accordance with PRISMA guidelines. Observational studies published between January 1, 2000, and March 31, 2024, were identified through searches of PubMed, Scopus, ScienceDirect, Web of Science, and Google Scholar, with the final search completed on April 30, 2024. Two reviewers independently extracted data, resolving discrepancies through consensus or consultation with a third reviewer. Prevalence estimates were pooled using a random-effects model, heterogeneity was quantified, and subgroup analyses and meta-regression were performed to explore sources of variability.ResultsSixteen studies comprised of 4,974 dogs across five states were included, and the pooled prevalence of canine Chagas infection was 12% (95% CI: 0.07–0.21), with significant heterogeneity (I2 = 96%). Louisiana had the highest pooled infection prevalence (18%; 95% CI: 0.04–0.51). Highest pooled infection prevalence was found among working dogs (32%; 95% CI: 0.07–0.74), while shelter dogs had the lowest (7%; 95% CI: 0.04–0.12). The meta-regression indicated that the study year was significantly associated with canine T. cruzi infection prevalence (p < 0.001), with an estimated 11% increase in odds per year, suggesting either a real temporal rise or improved detection/reporting over time.ConclusionThis review confirms the presence of canine T. cruzi infection in the U.S., though evidence is limited to a few southern states and marked by methodological variability. Standardized diagnostics, clearer dog type classification, and concurrent vector surveillance are needed to improve reliability and expand the geographic scope of future estimates.